Vertebral fracture assessment by DXA is inferior to X-ray in clinical severe osteoporosis. Issue 7 (July 2016) - Deleskog, L.; Laursen, N.; Nielsen, B.; Schwarz, P.
Abstract Summary Spine fractures are diagnosed by X-ray or vertebral fracture assessment (VFA) by dual-energy X-ray absorptiometry (DXA) scanning. The use of VFA evaluation by DXA is still debated. We demonstrate that VFA is inferior relative to X-ray in visualizing vertebrae properly in the upper spine and therefore with a reduced diagnostic performance in detecting fractures. Introduction Vertebral fracture assessment (VFA) by DXA has been evaluated for many years, and its use in clinical practice is still debated. In a cross-sectional setting, we aimed to compare VFA with traditional radiography in vertebral fracture (VF) diagnosis in severe osteoporotic patient. Methods A total of 207 patients referred to the outpatient clinic for teriparatide treatment were screened, out of whom 35 (16.9 %) severe osteoporotic patients were identified (mean age 67.5 ± 11.3 years and median T-score −3.2 interquartile range (IQR) (−1.9 to −3.7). VF diagnosis was performed independently using VFA and X-ray in accordance with the semiquantitative (SQ) approach. The same technician performed the primary interpretation on both sets of images, after which a radiologist and an endocrinologist reviewed the evaluation for a conclusive judgement. Results In total, 180 radiographic fractures were detected, corresponding to 5.1 fractures per individual. Using VFA, 18.5 % of vertebrae were considered unreadable, compared to 2.0 % on X-ray. The accuracy of VFA in VF detection using X-ray as a reference resulted in sensitivity and specificity of 75.5 and 86.7 %, respectively. Sensitivity decreased from the lumbar to thoracic level. Nevertheless, VFA only identified fractures consistently between Th11 and L3. Conclusion Our data, based on a severe osteoporotic population, demonstrate that VFA is inferior relative to X-ray in visualizing vertebrae properly in the upper spine, resulting in vertebrae not being assessable for analysis and a reduced diagnostic performance in detecting fractures. Improvements in DXA techniques are needed for it to be comparable with X-ray in VF diagnosis.